Genetic Trends for Racing Performance in Turk Arabian Horses Raised - kaygisiz, ali (The Indian Journal of Animal Sciences, 2011)
The aim of this study was to estimate genetic trends on racing performance of Turkish arabian horses raised at Anatolian Agricultural farms were investigated. The effects of year  on racing time and racing speed were found highly significant (P